Long-time existence for the semilinear Klein–Gordon equation on a compact boundary-less Riemannian manifold. Issue 3 (4th March 2017) - Delort, Jean-Marc; Imekraz, Rafik
ABSTRACT: We investigate the long-time existence of small and smooth solutions for the semilinear Klein–Gordon equation on a compact boundary-less Riemannian manifold. Without any spectral or geometric assumption, our first result improves the lifespan obtained by the local theory. The previous result is proved under a generic condition of the mass. As a by-product of the method, we examine the particular case, where the manifold is a multidimensional torus, and we give explicit examples of algebraic masses for which we can improve the local existence time. The analytic part of the proof relies on multilinear estimates of eigenfunctions and estimates of small divisors proved by Delort–Szeftel. The algebraic part of the proof relies on a multilinear version of the Roth theorem proved by Schmidt.